The Impact of a Community Partner Research Training Program - Oluwademilade Adefarati; Rickisa Yearwood; Yawei Song; Amy E. Leader; Karen Glanz; Evelyn T. Gonzalez; Scott W. Keith; Nilsa Graciani; Thierry Fortune; Charnita M. Zeigler-Johnson (Journal of Cancer Education, 2026)
As part of its mission to address disparities in cancer outcomes and research participation, the Philadelphia Communities Conquering Cancer (PC3) coalition conducted a Community Partner Research Training program. The goal was to increase knowledge about cancer research and to prepare community members to partner on research activities. Eighteen out of 36 applicants were selected for a 5-week training program on research methods. Trainees completed baseline ( N = 18) and follow-up surveys ( N = 10) to measure knowledge acquisition. Demographic data were analyzed with descriptive statistics. For repeated cross-sectional group comparisons, Wilcoxon nonparametric tests were used to test statistical differences between medians on baseline and follow-up surveys. P -values ≤ 0.05 were considered statistically significant. Trainees were mostly female (78%). Median age was 61.5 years. Forty-four percent were Black, 22% White, 17% Asian, and 17% other race. Twenty-eight percent were Hispanic. Forty-four percent were cancer survivors. We observed that perceived knowledge about research generally increased post-training from a median of 2 to 4 across a 5-point Likert scale ( p < 0.001). This increase is shown for several items, including “how to conduct a research study” and “how to share findings with the community.” Program ratings averaged 4 out of 5, indicating positive participant experiences in program organization and content. Involving diverse populations in cancer research is crucial for reducing health disparities. This training program demonstrated that it is feasible to increase knowledge about cancer research methodology among community partners. These results will be used to guide future research activities with PC3.